A survey on video segmentation for real-time applications - Maarif, Haris Al Qodri; Bilal, Sara Mohammed Osman Saleh; Gunawan, Teddy Surya; Khalifa, Othman Omran (IIUM Press, 2011)
Video object segmentation is to extract moving and static objects from consecutive video frames. It is a prerequisite for visual content retrieval (e.g., MPEG-7 related schemes), objectbased compression and coding (e.g., MPEG-4 codecs), object recognition, object tracking, security video surveillance, traffic monitoring for law enforcement, and many other applications